The Corrosion Behavior of Sputter-deposited W-Cr-(4-15)Ni Alloys in NaOH Solutions - Kharel, Pom Lal; Bhattarai, Jagadish (Journal of Nepal Chemical Society, 2009)
The synergistic effect of chromium addition in the sputter-deposited amorphous or nanocrystalline W-Cr-(4-15)Ni alloys is studied in alkaline NaOH solutions at 25°C, open to air using immersion tests and electrochemical measurements. In 1 M NaOH solution, the addition of chromium to W-Cr-(4-15)Ni alloys containing 42-75 at % chromium increased the corrosion resistance and shifted the open circuit potential more noble so as to show higher corrosion resistance than those of alloy-constituting elements (that is, tungsten, chromium and nickel). The corrosion rates (that is, about 2-5 x 10-3 mm.y-1) of all the examined W-Cr-(4-15)Ni alloys are about two orders of magnitude lower than that of tungsten and nearly one order of magnitude lower than that of chromium metal. The open circuit potential of the W-Cr-(4-15)Ni alloys is generally increased with increasing chromium content in different concentrations of NaOH solutions. The passivity of the WCr-(4-15)Ni alloys is increased with decreasing the concentration of NaOH solutions at 25°C. Keywords: Corrosion resistance; Sputter deposition; W-Cr-Ni alloy; NaOH solution; Open Circuit potential. DOI: 10.3126/jncs.v24i0.2380 Journal of Nepal Chemical Society, Vol. 24, 2009 Page: 3-11